PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2019-2022 - Reslianty Rachim; Rudy Syafariansyah; Abdul Rachim; Ahmad Surahman; Nur Nabila (OBOR: Oikonomia Borneo, 2024)
The aim of this research is to determine the effect of Current Ratio, Total Assets Turnover, Debt to Equity Ratio and Net Profit Margin on profit growth. The method used in this research is a quantitative research method. The sample in this study was selected using a purposive sampling technique, namely a sampling technique with certain criteria, so that a sample of 18 companies was obtained. The analytical method used in this research is multiple linear regression analysis. The research results state that the Current Ratio has no effect on profit growth, Total Assets Turnover has no effect on profit growth, Debt to Equity Ratio has no effect on profit growth, Net Profit Margin has an effect on profit growth. Current Ratio, Total Assets Turnover, Debt to Equity Ratio and Net Profit Margin simultaneously have no effect on profit growth